Putting Restraint on Chemical Restraint: Exploring the Complexity of Acute Inpatient Mental Health Nurses' Experience of Chemical Restraint Interventions - Michelle Danda (York University Libraries, 2020)
While there is a growing body of research available on general restraint intervention in acute adult psychiatric settings, relatively little is known about nurses' experiences of administering chemical restraint. The research question explored in this study was: what are mental health nurses' experiences of using chemical restraint interventions in times of behavioural emergency on adult inpatient acute mental health units? Through this Canadian study understanding of direct care nurses' first-hand experiences of the use of chemical restraint interventions was sought. Eight adult acute inpatient mental health nurses were interviewed using hermeneutic phenomenological method. Two major themes that emerged from data analysis are explored to illuminate the existing tension between therapeutic, person-centred care and coercive control to maintain safety: taking control to maintain safety and working within constraints. Integral ways that nurses make meaning from administering chemical restraint were found, as well as some of the complex clinical and ethical decision-making aspects involved in psychiatric nursing care. Implications for practice, education, and policy are discussed. Research findings indicated a need for further focus on medication best practice, policy development and nurse education. These exploratory research findings can be used to both inform and challenge dominant inpatient mental health practice to guide nurses, health care leaders, and policy makers by increased understanding of the complex ethical decision making required for use of chemical restraint interventions.